Implementasi Pendidikan Karakter Melalui Seven Habits (Studi pada TK. ABA Mantingan 3 Kabupaten Ngawi) - Sumarno, Sumarno; Wulandari, Nining (Proceedings of Annual Conference for Muslim Scholars, 2019)
The Character of education in schools is an effort by teachers to educate students have a better soul for them. The method used in this study is qualitative descriptive through a phenomenological approach with interview techniques, observations and documentation. In this research can be concluded that for the implementation of character education in TK. ABA Mantingan 3 through seven habits can be performed through some habituation including: first, shaking hands for coming and going home; second, reading before entering class; third, performing dhuha prayers; fourth, praying before learning; fifth, the movement of giving others; sixth, cheerful and healthy gymnastics activities; seventh, diligent movement of saving